Demand in Consumer Credit - Othman, Mohd Rashid (2010)
Consumer credit has witnessed a significant growth throughout the economic cycles. Sustained economic growth in Malaysia, averaging 5.9% a year over the past six years, has raised household incomes and boosted consumer confidence, which, in turn, has induced optimistic expectations of future income. The influence of macroeconomic variables toward the demand in consumer credit is inevitable as well as the performance of residential property transaction, automotive, credit cards usage and personal loans. Hence, this study aims to understand and explain the influence of these macroeconomic variables. Several analytical methods such as trend, correlation analysis and regressions were camed out. Some of the economic variables vary in the way they influence consumer credit but when GDP, BLR and unemployment increased it leads to decrease in demand of consumer credit while CPI and age group which are significantly positive correlated leads to increased of consumer credit. This finding suggests that by monitoring the macroeconomic variables, the demand in consumer credit may be predictable.